Synthesis of new hydrazone derivatives and evaluation of their monoamine oxidase inhibitory activity - KAYMAKÇIOĞLU, BEDİA; TOK, FATİH (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2021)
A novel series of hydrazone derivatives were designed and synthesized. Their structures were characterized by IR, 1H NMR, 13C NMR and HR-MS spectroscopic methods. The newly synthesized compounds were evaluated for their inhibitory activity against monoamine oxidase enzymes (MAO-A and MAO-B). Compounds 2a, 2k, 4a and 4i showed significant inhibitory activity against MAO-A, with IC50 value in the range of 0.084-0.207 mu M compared to reference drug moclobemide (IC50 value = 6.061 mu M). These compounds (2a, 2k, 4a and 4i) were exposed to cytotoxicity tests to establish their preliminary toxicological profiles and were found to be noncytotoxic. Moreover, the most effective compound 4i was evaluated using enzyme kinetics and docking studies to elucidate the plausible mechanisms of inhibition of MAO-A. According to enzyme kinetic studies, compound 4i was a reversible and competitive inhibitor with similar inhibition features as the substrates. Also, it was seen that this compound was settled down very properly at the active site of MAO-A enzyme by doing important interactions owing to the docking studies. Finally, ADME predictions were applied to estimate pharmacokinetic profiles of synthesized compounds. According to calculated ADME predictions, all parameters of the compounds were within the standard ranges in terms of Rule of Five and Rule of Three and it was detected that the synthesized compounds (2a-4i) have good and promising pharmacokinetic profiles.
Keywords: Hydrazone; Urea; MAO; Docking; ADME; MAO INHIBITORS; BIOLOGICAL EVALUATION; IN-VITRO; DESIGN; SOLUBILITY